AN APPROACH TO TECHNOLOGICAL EQUIPMENT SELECTION FOR MEASURING RAILWAY TRACK GEOMETRY - Gintautas BUREIKA (Transport Problems)
The most-used railway track geometry measurement systems are considered in this study. The advantages and disadvantages of considered systems and the necessity and application of these technologies in European railways were examined. The decisive factors of the operation of measurement equipment were considered. Real-time railway track condition monitoring systems were evaluated by 14 experts according to a scale of 13 criteria. Questionnaire data were processed using Kendall’s rank correlation method, and the mean ranks were normalized using the average rank transformation into weight method. The most relevant evaluation criteria describing the principles of operation and quality of the most promising technologies were defined. The most important criteria for assessing the suitability of technologies were determined by applying the technique for order of preference by similarity to ideal solution. Finally, basic conclusions and recommendations were formulated.